Is the routine health information system ready to support the planned national health insurance scheme in South Africa?. Issue 5 (2nd April 2021) - Nicol, Edward; Hanmer, Lyn A; Mukumbang, Ferdinand C; Basera, Wisdom; Zitho, Andiswa; Bradshaw, Debbie
Abstract: Implementation of a National Health Insurance (NHI) in South Africa requires a reliable, standardized health information system that supports Diagnosis-Related Groupers for reimbursements and resource management. We assessed the quality of inpatient health records, the availability of standard discharge summaries and coded clinical data and the congruence between inpatient health records and discharge summaries in public-sector hospitals to support the NHI implementation in terms of reimbursement and resource management. We undertook a cross-sectional health-records review from 45 representative public hospitals consisting of seven tertiary, 10 regional and 28 district hospitals in 10 NHI pilot districts representing all nine provinces. Data were abstracted from a randomly selected sample of 5795 inpatient health records from the surgical, medical, obstetrics and gynaecology, paediatrics and psychiatry departments. Quality was assessed for 10 pre-defined data elements relevant to NHI reimbursements, by comparing information in source registers, patient folders and discharge summaries for patients admitted in March and July 2015. Cohen's/Fleiss' kappa coefficients ( κ ) were used to measure agreements between the sources. While 3768 (65%) of the 5795 inpatient-level records contained a discharge summary, less than 835 (15%) of diagnoses were coded using ICD-10 codes. Despite most of the records having correct patient identifiers [ κ : 0.92; 95% confidence interval (CI) 0.91–0.93], significant inconsistencies were observed between the registers, patient folders and discharge summaries for some data elements: attending physician's signature ( κ : 0.71; 95% CI 0.67–0.75); results of the investigation ( κ : 0.71; 95% CI 0.69–0.74); patient's age ( κ : 0.72; 95% CI 0.70–0.74); and discharge diagnosis ( κ : 0.92; 95% CI 0.90–0.94). The strength of agreement for all elements was statistically significant ( P -value ≤ 0.001). The absence of coded inpatient diagnoses and identified data inaccuracies indicates that existing routine health information systems in public-sector hospitals in the NHI pilot districts are not yet able to sufficiently support reimbursements and resource management. Institutional capacity is needed to undertake diagnostic coding, improve data quality and ensure that a standard discharge summary is completed for every inpatient.